Interpreting the shared socio-economic pathways under climate change for the ECOWAS region through a stakeholder and multi-model process - Palazzo, Amanda; Vervoort, Joost M.; Mason-D'Croz, Daniel; Rutting, Lucas; Havlík, Petr; Islam, Shahnila; Bayala, Jules; Kadi Kadi Hame A.; Thornton, Philip K.; Zougmoré, Robert (2016)
In this paper, we present four globally-consistent regional scenarios on Western Africa’s development that have been used to test and develop a range of national and regional policies. The regional scenarios were outlined independently by regional stakeholders but built around the context of the SSPs. The scenarios were quantified using two agricultural models, GLOBIOM and IMPACT, in interaction with drivers outlined by the SSPs and guided by semi-quantitative information from the stakeholders.